Nitrogeniibacter aestuarii sp. nov., a Novel Nitrogen-Fixing Bacterium Affiliated to the Family Zoogloeaceae and Phylogeny of the Family Zoogloeaceae Revisited - Huang, Zhaobin; Liu, Renju; Chen, Fenghua; Lai, Qiliang; Oren, Aharon; Shao, Zongze (Frontiers in Microbiology, 2021)
Members of the family Zoogloeaceae within the order Rhodocyclales are found to play vital roles in terrestrial and aquatic ecosystems by participating in biofloc formation in activated sludge, polycyclic aromatic hydrocarbon degradation as well as the nitrogen metabolism, such as denitrification and nitrogen fixation. Here, two bacterial strains designated H1-1-2AT and ZN11-R3-1 affiliated to the family Zoogloeaceae were isolated from coastal wetland habitats. The 16S rRNA gene sequences of the two strains were 100% identical and had maximum similarity with Nitrogeniibacter mangrovi M9-3-2T of 98.4%, and other species of ≤ 94.5%. Phylogenetic analysis suggested that the two strains belonged to a single species and formed a novel monophyletic branch affiliated to the genus Nitrogeniibacter. The average nucleotide identity (ANI) value and digital DNA-DNA hybridization (dDDH) estimate between the two strains and N. mangrovi M9-3-2T were 78.5-78.7% and 21.4-21.6%, respectively, indicating that the two strains represent a novel species. The genomes of strain H1-1-2AT (complete genome) and ZN11-R3-1 (draft genome) were 4.7 Mbp encoding ~4,360 functional genes. The DNA G+C content was 62.7%. Nitrogen ﬁxation genes were found in the two strains, which were responsible for the growth on nitrogen-free medium, whereas denitrification genes found in N. mangrovi M9-3-2T were absent in the two strains. The respiratory quinone was ubiquinone-8. The major polar lipids consisted of phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylglycerol and aminophospholipid. The major fatty acids were summed feature 3 (C16:1ω7c and C16:1ω6c), C16:0, C12:0, and C10:0 3-OH. Based on genomic, phenotypic, and chemotaxonomic characterizations, strains H1-1-2AT and ZN11-R3-1 represent a novel species of the genus Nitrogeniibacter, for which the name Nitrogeniibacter aestuarii sp. nov. is proposed. The type strain is H1-1-2AT (= MCCC 1K04284T = KCTC 82672T) and a reference strain is ZN11-R3-1 (=MCCC 1A17971=KCTC 82671). Additionally, phylogenomic analysis of the members of the family Zoogloeaceae including type strains and uncultivated bacteria using the Genome Taxonomic Database toolkit (GTDB-Tk) were performed. Combined with the 16S rRNA gene phylogeny, four novel genera, Parazoarcus gen. nov., Pseudazoarcus gen. nov., Pseudothauera gen. nov., and Cognatazoarcus gen. nov. were proposed. This study provided new insights to the taxonomy of the family Zoogloeaceae.